2020
DOI: 10.1007/s41811-020-00088-1
|View full text |Cite
|
Sign up to set email alerts
|

Blended Treatment for Depressive Disorders in Youth: a Narrative Review

Abstract: Depressive disorders are the most prevalent mental health disorder in adolescents with detrimental consequences; effective and available treatment is crucial. Face-to-face and computerized treatments both have advantages but also downsides. Merging these two into one so-called blended treatment seems to be an optimal combination of elements. This current review addresses blended treatment for youth depression and aims to summarize existing knowledge on effectiveness as well as patients’ and therapists’ perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…These include, for example, telephone therapy (Brenes et al, 2015), therapy delivered via texting (Snoswell et al, 2021) and internet-based therapy (Barak et al, 2008;Välimäki et al, 2017). As indicated in Barak et al (2008) interactions with therapists and e-contents) and application-based therapeutic activities, also known as 'apps for mHealth' (mobile health) (Rasing, 2021). Smartphone apps, in specific, appear to be an increasingly popular digital way of accessing readily available mental health support, due to their 24-h availability, unique characteristics and increased connectivity, have been suggested to be a beneficial method for therapeutic delivery (Grist et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include, for example, telephone therapy (Brenes et al, 2015), therapy delivered via texting (Snoswell et al, 2021) and internet-based therapy (Barak et al, 2008;Välimäki et al, 2017). As indicated in Barak et al (2008) interactions with therapists and e-contents) and application-based therapeutic activities, also known as 'apps for mHealth' (mobile health) (Rasing, 2021). Smartphone apps, in specific, appear to be an increasingly popular digital way of accessing readily available mental health support, due to their 24-h availability, unique characteristics and increased connectivity, have been suggested to be a beneficial method for therapeutic delivery (Grist et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, clinician‐delivered digital interventions are not the only form of therapeutic support available, as there is a growing interest, particularly in younger generations, in new forms of digital interventions, including ‘blended interventions’ (encompassing live interactions with therapists and e‐contents) and application‐based therapeutic activities, also known as ‘apps for mHealth’ (mobile health) (Rasing, 2021). Smartphone apps, in specific, appear to be an increasingly popular digital way of accessing readily available mental health support, due to their 24‐h availability, unique characteristics and increased connectivity, have been suggested to be a beneficial method for therapeutic delivery (Grist et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, applying the Res@t app with its up-to-date treatment material within a blended therapy context might enrich and facilitate face-to-face interventions and allow multiple self-guided repetitions to consolidate content. Reviews suggest positive effects of such an approach across age groups including adolescent patients ( 73 , 74 ) with evidence of beneficial effects of guided (versus unguided) digital interventions ( 75 ). Moreover, the beneficial effects of additional face-to-face interventions are assumed to vary according to the reachability of adolescents with DMUD.…”
Section: Discussionmentioning
confidence: 99%
“…A previous review demonstrated that the use of blended treatment for adolescents with a depressive disorder largely depends on acceptance by therapists as well as by patients [ 36 ]. It is likely that this acceptance increases with more insight into the effectiveness and risks of blended CBT.…”
Section: Discussionmentioning
confidence: 99%
“…Two randomized controlled trials by Topooco et al [ 34 , 35 ] showed that an online program including eight weekly chat-sessions resulted in significantly lower depressive symptoms when compared to control conditions comprising active monitoring or non-specific counseling. Although these findings provide a positive perspective on blended CBT, it is unknown whether not seeing patients face-to-face regularly increases the risk of adverse events including suicide risk [ 36 ], and whether the presented effects can be translated to adolescents treated in routine care.…”
Section: Introductionmentioning
confidence: 99%